An Investigation into Cultural Representation in Interchange Textbooks - Ali Roohani; Elham Molana (Issues in Language Teaching, 2013)
Language and culture are now deemed to be co-constitutive; hence English language teaching (ELT) textbooks should incorporate cultural aspects and promote intercultural competence. However, careful decisions should be made as regards to the cultural content of materials and the ways in which culture is represented. This study was an attempt to deconstruct the patterns of cultural representation and intercultural interactions in Interchange textbooks, an ELT textbook series taught to English as a foreign language (EFL) learners in Iran. Using content analysis of texts and images and with the focus on nationality, gender and race, it examined how different cultures were reflected in Interchange 1, Interchange 2, Interchange 3, and whether cultural bias or inequality was present. The quantitative and qualitative data analysis revealed that the white male group was dominant in all three textbooks. And, to use Kachru’s (1985) terms, inner, outer and expanding circle nationalities were represented in the textbooks, with the expanding circle constituting the major nationality, but American culture of inner circle was predominant. Additionally, the interactions were mainly limited to superficial aspects of the target culture although these textbooks sought to show various intercultural interactions. Dominance of male and white characters and the US culture indicated inequality in race and gender, and the superficial treatment of culture in the textbooks. Less attention to the hybrid culture and deeper level of intercultural aspects, i.e. critical reflections, in the textbooks suggests that the materials be supplemented by EFL teachers’ constructive discussion of the cultures that interact.